Implementation of the Team Based Learning Model in Improving Student Learning Outcomes in the Trigonometry Course - Nur Elisyah; Mutia Fonna; Mursalin Mursalin (Electronic Journal of Education, Social Economics and Technology, 2026)
The purpose of this study is to analyze the improvement of student learning outcomes after the implementation of the team-based learning model in trigonometry courses. This study employs a classroom action research method, in which the implementation involves four key steps: 1) planning, 2) execution, 3) observation, and 4) reflection. This research was conducted at the Faculty of Teacher Training and Education, Universitas Malikussaleh. The sample in this study were 36 students of the Mathematics Education Study Program. The cycle in this classroom action research consists of two cycles (Cycle I and Cycle II). In the implementation of cycles I and II using a team-based learning model with the following stages: 1) preparation, 2) Readiness Assurance, 3) Application of Course Concepts, 4) Instructor Feedback.  This study employs data collection methods consisting of test instruments to assess students’ learning outcomes and observation sheets to monitor student activities throughout the instructional process. The results of the data analysis show that the completeness of student learning outcomes before the action or pre-cycle was 44.44%.  Following the application of the team-based learning model in Cycle I, there was an increase to 97.22% and cycle II increased to 100%. So, it can be concluded that the team-based learning model improves student learning outcomes in trigonometry courses and encourages active participation in the learning process.